Accumulation and Distribution of Heavy Metals in Green-Lipped Mussel Perna Viridis (Linnaeus) from the West Coast of Peninsular Malaysia - Yap, Chee Kong (1999)
The main aim of this study is to establish mussel Perna viridis as a biomonitoring agent along the west coast of Peninsular Malaysia. In this study, the levels of heavy metals had been studied in the mussel P. viridis collected from 13 stations along the coastline of Peninsular Malaysia and 2 stations in Sabah. The results showed that, in general, the levels of heavy metals in total soft tissue of mussel P. viridis were within or lower than the levels found elsewhere. The ranges varied widely from 0.19 to 1.56 µg.g⁻¹ dry weight for Cd, 5.78 to 15.14 µg.g⁻¹ dry weight for Cu, 1.17 to 8.27 µg.g⁻¹ dry weight for Pb and 46.78 to 145.95 µg.g⁻¹ dry weight for In. Mussels P. viridis collected from one population were dissected into eight parts (byssus, mantle and gills, posterior adductor muscle, retractor byssal muscle, foot, crystalline style, gonad and remainder visceral mass) and the concentrations of heavy metals were measured. The highest concentration of Cu was obtained in the crystalline style while elevated Cu, Pb and Zn concentrations were noted in the byssus. Female's gonad generally accumulated higher metals levels than male's gonad. In the study of different parts in the shen of mussel P. viridis, eu and Zn levels were found elevated in the periostracum layer while Cd and Ph levels were highly elevated in the inner nacreous shenlayer. The relationships between the concentrations (µg.g⁻¹) and contents (µg.individual⁻¹) of heavy metals and body size (total STI dry weight, shell thickness and sheD length) were also investigated. The results indicated that smaller mussels have higher metals accumulation especially for Cd, Zn and Pb. The metal accumulations in total STI of P. viridis were also affected by metal concentrations in sediment and suspended particulate materials. Besides, physico-chemical parameters, condition in4ex, population structure and sex also played a role in affecting heavy metal accumulation in mussel P. viridis. Apart from Sn mussel sheD and byssus also can be considered as good bioindicators for Cu, Zn, Cd and Cu. Pearson's correlation coefficients in these metals in the organs showed positive correlations and suggested the organ to be a goosd bioindicator. The study on coefficient of variation indicated that if analysis of individuals are used, a very limited size range of samples from all stations should be selected to increase the ability of biomonitoring programmes. In general, this study showed that ell, Pb, Zn and Cd accumulated in the STI of P. viridis and showed some agreements that P. viridis is a good bioindicator for ell, Pb, Zn and Cd. Tissue distribution of Cll, Ph, Zn and Cd varied in the organs and this phenomenon probably depends on physiology, ecology and biology of the mussel P. viridis.